Meaning-centered Learning in Islamic Religious Education in Western Societies - Jörg Imran Schröter (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
The introduction of Islamic religious education in public institutions across Western societies poses a challenge for Islamic pedagogy, requiring it to integrate classical Muslim religious knowledge with contemporary educational frameworks and pedagogical standards. This article aims to develop a meaning-centered, learner-oriented conceptual approach to Islamic religious education in school and higher education contexts in the West. Employing a conceptual-reflective methodology, the study draws on a critical analysis of relevant literature in Islamic studies, religious education, and educational theory, complemented by scholarly reflection on more than fifteen years of teaching experience in Islamic religious education. The analysis demonstrates that Islamic religious education in public institutions cannot be reduced to catechetical instruction; rather, it should be understood as a pedagogical process fostering students' religious maturity, encompassing reflective competence, linguistic articulation, and self-determination. Based on this perspective, the article proposes a meaning-centered framework of religious learning conceptualized as a hermeneutical process in which learners actively construct the meaning of religious content. The article concludes that such a framework provides a pedagogically sound and context-sensitive foundation for Islamic religious education in Western societies. Theoretically, it contributes to ongoing debates in Islamic educational pedagogy, while, practically, it offers implications for teacher education and curriculum development in Islamic religious education within public educational systems.